'STFU and start listening to how scared we are': Resisting misogyny on Twitter via #NotAllMen. (June 2022) - Jones, Lucy; Chałupnik, Małgorzata; Mackenzie, Jai; Mullany, Louise
Abstract: This article focuses on the strategies that were used to resist misogyny on the microblogging platform Twitter during March 2021, a time when the hashtag #NotAllMen was trending. We take a critical feminist approach, combining corpus linguistics with a qualitative analysis of #NotAllMen users' discursive strategies. This particular iteration of #NotAllMen followed the disappearance and subsequent rape and murder of Sarah Everard, a 33 year old white woman who was abducted from a street in London, UK, whilst walking home. Following a keyword analysis (Scott 1997) to survey a dataset of 18, 701 tweets containing the hashtag #NotAllMen, we identify salient themes in a sub-set of keyword concordances, and produce a detailed qualitative analysis of the strategies deployed in ten randomly sampled tweets. Despite #NotAllMen initally being used as a statement of protest against supposedly unfair accusations levelled at 'all' men, our analysis illustrates the use of resistant and empowering strategies which challenge the misogyny of this message, re-framing the hashtag and thus acting as a form of resistance to its original message: that not all men enagage in gender-based violence. We argue that this points to the strategic use of social media to challenge harmful rhetoric, whereby users exploit the affordances of hashtags. Twitter users engaged in strategies including resistance, opposition, and polarity to the hashtag, evidenced through the linguistic use of expletives, insults, and direct address, most often emerging through metadiscussion of the #NotAllMen hashtag itself; this works as a form of collective counter-protest through hashtag reframing. The hashtag reframing operates as a tool to show how those using the hashtag to focus on the defence of men, rather than critiquing the sociocultural dominance of misogynistic behaviour, ignored the fear experienced by all women and girls of being victims of gender-based violence, rape and murder.